Rome's Christian empress : Galla Placidia rules at the twilight of empire - Salisbury, Joyce E. (Baltimore : Johns Hopkins University Press, 2015)
"In Rome's Christian Empress, Joyce E. Salisbury brings the captivating story of Rome's Christian empress to life. The daughter of Roman emperor Theodosius I, Galla Placidia lived at the center of imperial Roman power during the first half of the fifth century. Taken hostage after the fall of Rome to the Goths, she was married to the king and, upon his death, to a Roman general. The rare woman who traveled throughout Italy, Gaul, and Spain, she eventually returned to Rome, where her young son was crowned as the emperor of the western Roman provinces. Placidia served as his regent, ruling the Roman Empire and the provinces for twenty years. Salisbury restores this influential, too-often forgotten woman to the center stage of this crucial period. Describing Galla Placidia's life from childhood to death while detailing the political and military developments that influenced her--and that she influenced in turn--the book relies on religious and political sources to weave together a narrative that combines social, cultural, political, and theological history. The Roman world changed dramatically during Placidia's rule: the Empire became Christian, barbarian tribes settled throughout the West, and Rome began its unmistakable decline. But during her long reign, Placidia wielded formidable power. She fended off violent invaders and usurpers who challenged her Theodosian dynasty; presided over the dawn of the Catholic Church as theological controversies split the faithful and church practices and holidays were established; and spent fortunes building churches and mosaics that incorporated prominent images of herself and her family. Compulsively readable, Rome's Christian Empress is the first full-length work to give this fascinating and complex ruler her due"--
Includes bibliographical references and index.
Print version record.
Keywords: Galla Placidia, -- Empress, -- approximately 386-450.; Empresses -- Rome -- Biography; Regents -- Rome -- Biography; Christian biography -- Rome; Women -- Political activity -- Rome -- History; Social change -- Rome -- History; Rome -- History -- Valentinian III, 425-455.; Rome -- History -- Empire, 284-476.; Rome -- History -- Germanic Invasions, 3rd-6th centuries; HISTORY / Ancient / General; RELIGION / General; LITERARY CRITICISM / Ancient & Classical; SOCIAL SCIENCE / Women's Studies; Galla Placidia, -- Empress, -- approximately 386-450.; Christian biography; Empresses; Regents; Social change; Women -- Political activity; Rome (Empire); BIOGRAPHY & AUTOBIOGRAPHY / Historical; HISTORY / Ancient / Rome; Biography; History; Electronic books